1970
DOI: 10.3126/kumj.v8i2.3552
|View full text |Cite
|
Sign up to set email alerts
|

Surgical abortion in second trimester: Initial experiences in Nepal

Abstract: Introduction: In spite of legalising abortion and making safe abortion available at affordable price at accessible distance to almost everyone, unsafe abortion especially second trimester abortion is still a big health problem in Nepal. Objective: The objective of the study is to fi nd the demographic profi le, reasons for seeking abortion and to see the effectiveness of Misoprostol in preparing the cervix. Materials and methods: A prospective study was done in the two second trimester abortion trainings condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
4
6
0
Order By: Relevance
“…In that study 84% were multipara, gestational age range was 12-24 weeks and 56% were between 12-14 weeks. 10 In our study success was 90.58% (n=462), expulsion with total five doses of misoprostol which is comparable to 91.4% in a study from Hong Kong 11 and 97% in a study from Scottland. 7 There were 70.93% (n=383) clients who were multiparous, 82.04% (n=443) wanted abortion due to mental ill-health and 11.85% (n=64) were unmarried in comparison to a study from Nepal where multiparity was 61.4% and 5.26% were unmarried.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In that study 84% were multipara, gestational age range was 12-24 weeks and 56% were between 12-14 weeks. 10 In our study success was 90.58% (n=462), expulsion with total five doses of misoprostol which is comparable to 91.4% in a study from Hong Kong 11 and 97% in a study from Scottland. 7 There were 70.93% (n=383) clients who were multiparous, 82.04% (n=443) wanted abortion due to mental ill-health and 11.85% (n=64) were unmarried in comparison to a study from Nepal where multiparity was 61.4% and 5.26% were unmarried.…”
Section: Discussionsupporting
confidence: 73%
“…7 There were 70.93% (n=383) clients who were multiparous, 82.04% (n=443) wanted abortion due to mental ill-health and 11.85% (n=64) were unmarried in comparison to a study from Nepal where multiparity was 61.4% and 5.26% were unmarried. 10 The median induction to abortion time was 4-7 hours. The expulsion hours increased, as the gestational age increased as the study showed median induction to abortion time for more than 24 weeks was 9 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the maternal mortality ratio declined from 539 to 281 deaths per 100,000 live births between 1996 and 2006 (5) while abortion-related complications fell from constituting 54% to 28% of all maternal morbidities between 1999 and 2008. (6,7) Despite this considerable progress of enhancing the use of official and safe abortion services, unsafe abortions are still a major issue in Nepal as it has been estimated that they constitute half of all abortions undertaken every year. In a study from 2008, it was estimated that at least 97,400 safe abortions occurred in Nepal that year but also that "[...] the number of abortions performed by unregistered providers in 2008 was likely equal to those done by registered providers".…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, a study showed that 36% of women between 25 and 29 years of age seek induced abortion (Thapa & Padhye, 2001). In Nepal, common reasons for seeking induced abortion are multiple pregnancies (61.4%), completed desired family size (61.4%), unwanted pregnancy in marriage (10.52%), unintended pregnancy in unmarried young women (5.26%) and a desire to have a son instead of a daughter (Puri et al, 2007;Dawadi & Shrestha, 2007;Shrivastava, Bajracharya & Thapa, 2010& Bhattarai, 2011.…”
Section: Significance Of Problem the Prevalence Of Induced Abortion mentioning
confidence: 99%